The influence of human resource practices on service recovery performance: A comparison between Thais and the Filipino customer contact agent - Oentoro, Wanny; Villegas-Puyod, Jenette (Kasetsart Journal of Social Sciences, 2023)
This research aimed to study the impact of HR practices toward client contact agents’ service recovery performance (SRP) in two Southeast Asia countries, namely, Thailand (THA) and The Philippines (PHL). As a customer contact agent is the first port that addresses dissatisfied customers, it is important to know the dynamics that may affect the service performance. More precisely, the current research compares Thai and Filipino customer contact representatives’ service recovery performance. The two nations are most attractive top targets for call center service subcontracts. In total, there were 2,350 completed surveys. The study employed PLS-SEM and independent sample T-test to test for hypotheses and additional findings. The results confirmed the influence of HR practices on the SRP of workforces and illustrated the difference between the countries. It revealed that the relationships were statistically low for Thai contact representatives when being compared to Filipino contact agents. Therefore, it is recommended that managers contemplate HR practices together with considering ethnicity and cultural diversity. Henceforth, to perform better in a cross-cultural setting, cultural training and communication competency training may aid the management to understand their service employees of what will facilitate them to satisfy the customer’s inquiries and recover unsatisfied customers.